The GRENE-TEA model intercomparison project (GTMIP) Stage 1 forcing data set - Sueyoshi, T.; Saito, K.; Miyazaki, S.; Mori, J.; Ise, T.; Arakida, H.; Suzuki, R.; Sato, A.; Iijima, Y.; Yabuki, H.; Ikawa, H.; Ohta, T.; et al. (Earth System Science Data, 2016)
Here, the authors describe the construction of a forcing data set for land surface models (including both physical and biogeochemical models; LSMs) with eight meteorological variables for the 35-year period from 1979 to 2013. The data set is intended for use in a model intercomparison study, called GTMIP, which is a part of the Japanese-funded Arctic Climate Change Research Project. In order to prepare a set of site-fitted forcing data for LSMs with realistic yet continuous entries (i.e. without missing data), four observational sites across the pan-Arctic region (Fairbanks, Tiksi, Yakutsk, and Kevo) were selected to construct a blended data set using both global reanalysis and observational data. Marked improvements were found in the diurnal cycles of surface air temperature and humidity, wind speed, and precipitation. The data sets and participation in GTMIP are open to the scientific community (doi:10.17592/001.2015093001).